The Zootechnical Factors Affecting the Biosecurity Profile of Fish Farms in the Centre Region of Cameroon: Biosecurity Profile of Fish Farms in the Centre Region of Cameroon - Fonkwa, Georges; KPOUMIE NSANGOU , Amidou; Makombu, Judith Georgette; KAMETIEU DJAMOU, Franck Junior; Tomedi Eyango, Minette; Tchoumboue (Journal of Aquaculture and Fish Health, 2024)
In order to optimize the fish production by a better knowledge of preventive measures against fish diseases, a cross-sectional audit was carried out in Cameroon from March to April 2022 on the zootechnical factors affecting the biosecurity practice in fish farms from the Centre Region (3°55'- 4°67'N; 9°46-11°52'E). A total of 50 farms were selected using the "snowball" method, face-to-face interview of fish farmers using a semi-structured questionnaire and direct observation. The most practiced farming system was the semi-intensive production system (74%), non-integrated fish farming (100%), grow-out (66%), monoculture (54%), and the soil system (34% of farms with ponds). The compliance rate (40.98%) and adoption rate (41.00%) of biosecurity measures (BM) was intermediate. The most adopted BM were "sanitary lock" and "no exchange of materials with other farms", while the least adopted were "veterinary intervention", "dead fish incinerated" and "special outfit for visitors". The BM were significantly more observed in intensive, nursery farms and those whose culture facilities were fastanks + concrete tanks with 3 to 12 production cycles per year. A strong, positive and significant linear relationship was established between the compliance rate (y) and BM such as the protection of farms from wild animals, quarantine of new fish, number of production cycles per year (x). The linear regression model between y and x was y = 4.65x - 0.0417. The capacity of fish farmers should be built on biosecurity practices. Key words: Biosecurity practice, diseases, mortality, fish, Cameroon